A personalised search approach for web service recommendation. (30th May 2013) - Hu, Rong; Dou, Wanchun; Liu, Jianxun
It is a challenge to recommend services according to users' interests when search systems return plenty of keyword–like services. We propose a personalised search approach for web service recommendation. First, interests are extracted from users' records. Second, interest–similar users are selected using the criterion of cosine distance. Third, services are ranked in decreasing order based on the recommendation from interest–similar users. At the end of this paper, we conduct three groups' experiments to verify the effect of this approach.